Revisión teórica de los factores culturales organizacionales y psicosociales para una implantación exitosa de empresas extranjeras en México (Theorical review of cultural and psychosocial organizational factors for a successful implementation of foreign companies in Mexico) - González Salinas, Rubén Carlos; Blanco Jiménez, Mónica (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract. When foreign companies established in a new country, there are cultural differences that affect employee productivity. Both foreign and local employees will affect the psychological effects caused by culture shock, which leads to loss of productivity resulting mainly during the start up phase of operations. There are already several studies about the psychological level factors that negatively affect productivity in enterprises and organizational cultural factors which have an impact on the implementation of these companies.So it is obvious and possible generation of a culture shock in foreign companies operating in Mexican territory. In this case, this article seeks to make a theoretical review of the relationship between the level of culture shock that is generated in the interaction of employees from different cultures and/or nationalities. We analyze theoretically the organizational cultural and psychological factors that may affect the employee's performance to be considered by management of foreign companies established in Mexico, and that will allow to minimize the negative impact on organizational effectiveness.